Efecto del programa tutorial para el mejoramiento de la orientación vocacional en los estudiantes del quinto de secundaria del colegio Mariscal Oscar Raimundo Benavides, Iquitos 2023 - Castilla Rojas, Tatiana Rocio (2024)
The objective of the study was: To evaluate the effectiveness of the tutorial program in improving the vocational orientation of students in the fifth of secondary at Colegio Mariscal Oscar Raimundo Benavides, Iquitos 2023 School. The study was of an evaluative type, of cuasi-experimental design, with a sample of 145 students (73 in the experimental group and 72 in the control group), who were selected intentionally and voluntarily, with prior informed consent, to whom a questionnaire was administered to measure vocational orientation. The results showed that the two groups were at the same level of vocational orientation before starting the program. In the post-test, the average score obtained in vocational orientation was higher in the experimental group than in the control group (53.68 > 22.87). The analysis of the 4 dimensions of the variable vocational orientation, by means of the Mann-Whitney U test, reveal that the application of the tutorial program significantly improves the vocation and sociocultural importance, the factors that influence the vocation of the students, the vocational maturity and the motivations and professional interests of the student subjects of the sample; therefore, the 4 specific hypotheses formulated are accepted (p-value =0.000